2018
DOI: 10.3390/en11051064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Technologies for Integrated Solar Combined Cycles: Analysis of Concentrating Technology and Solar Integration

Abstract: This paper compares the annual performance of Integrated Solar Combined Cycles (ISCCs) using different solar concentration technologies: parabolic trough collectors (PTC), linear Fresnel reflectors (LFR) and central tower receiver (CT). Each solar technology (i.e. PTC, LFR and CT) is proposed to integrate solar energy into the combined cycle in two different ways. The first one is based on the use of solar energy to evaporate water of the steam cycle by means of direct steam generation (DSG), increasing the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Almeria and Las Vegas were the sites selected for the analyses of the proposed configurations [ 7 ]. A typical meteorological year (TMY) was used for both sites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Almeria and Las Vegas were the sites selected for the analyses of the proposed configurations [ 7 ]. A typical meteorological year (TMY) was used for both sites.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis led to 538 operating conditions in Almeria and 909 in Las Vegas. An example of these matrices is found in [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there were several simulation studies concerning solar energy [40,41] and collectors [42], as well as research evaluations [43]; however, there is a lack of examples of long-term operation in real and non-experimental conditions. The novelty of this paper is in its evaluation of two existing installations.…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al analyzed solar thermal technologies current status and research trends and concluded that direct steam generation by employing solar energy in solar concentrated schemes is the most promising approach. Rovira et al compared different technologies for integration is solar combined cycles. Hansen and Van Mathiesen presented a novel approach to evaluate the potential of utilizing solar thermal technologies in the Europe and assessed four countries (Germany, Austria, Italy, and Denmark) statuses of employing renewable energies, specifically solar thermal energy, to achieve European defined targets.…”
Section: Introductionmentioning
confidence: 99%